Effect of Topographical Features on the Growth and Yield of the Leaves of Sesbania Grandiflora L. Pers of Gunjur Region, Chikkaballapur District, Karnataka.: Life Sciences-Botany for Medicinal science - S. P, Naveen Kumar; Maya, C. (International Journal of Life Science and Pharma Research, 2021)
The leaves of Sesbania grandiflora L. Pers were collected from the Gunjur region of Chikkaballapur district and subjected to analysis for checking the growth. The data of the area regarding height in terms of growth, texture determining the soil type, rainfall occurred during the study duration, numbers of leaves per plant were recorded for quarterly analysis viz., March, June, September, and December 2020. The average yield was estimated according to the total number of plots of land utilized for cultivation. The phytochemicals present in these samples were evaluated for their presence. Overall features affecting the growth and yield were interpreted based on the survey. The present study focuses on the consistancy of the yield of the leaves of the plant Sesbania grandiflora L. Pers irrespective of the changes in the topography of Gunjur region, Chikkaballapur district, Karnataka State.